Menanam Nilai Ekosufisme dalam Pendidikan Dasar untuk Meningkatkan Kepedulian Lingkungan - Siti Lutfiatul Muhamaliah; Shafira Aulia Agustin; Ilma Alfiyanti; Muhammad Ramadhon Habibullah (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Exploration of the application of ecosufism values in basic education as an effort for students to increase environmental awareness. Ecosufism, which integrates the principles of Sufism with ecological awareness, offers a holistic approach to humans' relationship with nature. This research identifies and analyzes various strategies that can be implemented in the basic education curriculum, including project-based teaching, outdoor activities, and the integration of spiritual values in environmental learning. This research aims to increase environmental awareness. This is done by integrating spiritual awareness of nature into the educational curriculum, so that students understand the relationship between God, humans and the environment. This research uses qualitative research methods. The subjects of the research were teachers and students of MI Al-Ikhlas Ds. Mlaten District. Kalitidu District. Bojonegoro. The research results show that instilling ecosufism values not only increases students' understanding of environmental issues, but also forms positive attitudes and sustainable pro-environmental behavior. Therefore, this research recommends the development of educational programs that prioritize ecosufism values as a strategic step in creating a generation that is more concerned and responsible for the environment.